Microplastic Contents in Kijing Shells (Pilsbryoconchaexilis) in Tallo Makassarriver, Indonesia - Yuliati; Anwar Daud; Anwar Mallongi; Burhanuddin Bahar; Mukono; Mahatma Lamuru; Maming (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background : Plastic pollution in the aquatic environment has become a global concern because of its detrimental impact on river and marine ecosystems. Plastic waste that breaks down into plastic particles of microplastic size (less than 5 mm), allows fine particles to enter the food chain and leads to humans as top predators in the food chain.The purpose of this study was to determine the microplastic content of Kijing Shells (Pilsbryoconchaexilis) in the Tallo Makassar River.Methods: This type of research is observational with a laboratory approach using Minitab 16 software to determine the microplastic content of Kijing Shell (Pilsbryoconchaexilis) in the Tallo Makassar River.Results: The results of this study indicate that the abundance of microplastics in Kijing Shells (Pilsbryoconchaexilis) at station I is 5.6 Mps/Ind, station II is 2.2 Mps/Ind and station III is 1.8 Mps/Ind. For contaminants, station I was 100%, station II was 80% and station III was 60%. The most types of microplastics were line and fragment types, while the most common microplastics found were red, blue and gray. Conclutions: Kijing Shells (Pilsbryoconchaexilis) originating from the Tallo River, Makassar contain microplastics. The highest abundance of microplastics was at station I at 5.6 Mps/Ind, station II at 2.2 Mps/Ind and station III at 1.8 Mps/Ind. For contaminants, station I was 100%, station II was 80% and station III was 60%.